Introduction to Skin Cancer: A Video Module - Jasmine Rana; Arash Mostaghimi (Association of American Medical Colleges, 2016)
Abstract Introduction This introductory skin cancer video module engages novice health care professionals to make histological-clinical correlations for the three most common skin cancers: basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and melanoma. The goal of this video module is to engage novice health care professionals (e.g., allied health, medical, nursing students) to go beyond the all-too-common phenomenon of memorizing gross and histological features of skin cancers without reference to the relationship between these features. Methods By explicitly highlighting underlying histological-clinical correlations for BCC, SCC, and melanoma, this video module helps learners build a deeper and lasting knowledge of these common diseases. Materials in this module include a learner guide with instructions on how to complete the module; four chalk-talk videos that discuss classification of skin cancers, histological-clinical correlations for BCC, SCC, and melanoma, and how to distinguish among benign nevi, dysplastic nevi, and melanoma (total viewing time 54 minutes, 22 seconds); annotated slides used in the videos; and 10 multiple-choice self-assessment questions. Results This module was successfully incorporated into the first-year flipped classroom curriculum for medical and dental students at Harvard Medical School. Written comments from students revealed that they enjoyed watching short concept videos to prepare for in-class, case-based discussions of BCC, SCC, and melanoma. Discussion By illustrating histological-clinical correlations and reducing cognitive load of the material through use of cartoons and prototypical clinical images, this video module is an accessible initial resource for an emerging generation of millennial health care professionals to learn about common skin cancers.